Assessment of the Data Quality in Demographic and Health Surveys in Egypt - Zakarya Al Zalak; Anne Goujon (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2017)
The aim of this paper is to check the quality of fertility data collected through Demographic and Health Surveys in Egypt between 1988 and 2014. We are particularly interested to assess whether fertility changes observed since 2000 that point at a stall in fertility decline followed by a substantial increase between 2008 and 2014 are real and not due to imperfect data. We show through several exercises that data quality has increased since the first Demographic and Health Survey in 1988 and that the data imperfections do not explain the fertility trajectories in Egypt.
Keywords: 300; Egypt; Demographic and Health Surveys; data quality